2010
DOI: 10.1007/s00382-010-0802-6
|View full text |Cite
|
Sign up to set email alerts
|

200 years of European temperature variability: insights from and tests of the proxy surrogate reconstruction analog method

Abstract: Spatially resolved climate reconstructions are commonly derived from long instrumental series and proxy data via linear regression based approaches that use the main modes of the climate system. Such reconstructions have been shown to underestimate climate variability and are based upon the assumption that the main modes of climate variability are stationary back in time. Climate models simulate physically consistent climate fields but cannot be taken to represent the real past climate trajectory because of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 83 publications
3
43
0
Order By: Relevance
“…6). This finding is in line with other studies (Brönnimann and Luterbacher, 2004;Rutherford et al, 2005;Franke et al, 2010;Griesser et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…6). This finding is in line with other studies (Brönnimann and Luterbacher, 2004;Rutherford et al, 2005;Franke et al, 2010;Griesser et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…First attempts to assimilate climate proxy information into models include the pioneering work of von Storch et al (2000), Hargreaves and Annan (2002), van der Schrier and Barkmeijer (2005), Goosse et al (2006Goosse et al ( , 2010, and Franke et al (2010). The proposed approaches can be roughly separated into three groups: the methods of von Storch et al and van der Schrier and Barkmeijer seek to push a model simulation towards a large-scale target state through nudging (von Storch et al, 2000) or using singular forcing vectors (van der Schrier and Barkmeijer, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been implemented in a variety of applications in climate research, from hurricane prediction (Sievers et al, 2000;Fraedrich et al, 2003) to downscaling (Zorita and von Storch, 1999) and upscaling Schenk and Zorita (2012) techniques. For the interest of this study, the suitability of this technique to generate CFRs has been recently demonstrated for temperature (Franke et al, 2010) and precipitation (Gómez-Navarro et al, 2014) for Europe. Although the method is explained elsewhere, we briefly outline its key ideas here, following the notation by Gómez-Navarro et al (2014).…”
Section: The Am As Reconstruction Techniquementioning
confidence: 99%
“…Furthermore, Nicault et al (2008) used a pseudo-proxy approach similar to the one we use through this work to assess the performance of the reconstruction. In this work, we use the AM to produce a CFR reconstruction following an approach similar to Franke et al (2010) and more recently Gómez-Navarro et al (2014). Used in this way, the method uses a data-based approach to represent the spatial co-variability in the climate fields.…”
Section: Introductionmentioning
confidence: 99%